تجديد الخطاب الدعوي المعاصر: محمد الغزالي – أنموذجا - قواو عبد الحق (University Of Eloued جامعة الوادي, 2023)
الخطاب الدعوي المعاصر جهد بشري في سبيل بيان كليات الإسلام ومقاصده على مستوى الفرد والجماعة، ويمكن وصفه بأنه المدارسة الدائمة لمختلف الوقائع والاحداث على مسرح التاريخ الإنساني، ومحاكمتها إلى قيم ومقاصد الشريعة الخاتمة، انطلاقا من الخاصية القائمة فيها أصالة-الثبات والمرونة-، ثبات في المبادي والقيم والأصول ومرونة في الفروع والوسائل، وفق قواعد معرفية حضارية صارمة، مؤصلة بنصوص الوحي، متفاعلة مع المتغيرات والمستجدات في مختلف الشؤون والقضايا. حمل الخطاب الدعوي للشيخ محمد الغزالي ثراء معرفيا يضاف إلى رصيد الدعوة الإسلامية، وفيه محاولات جادة ووازنة في توجيه مسار الدعوة الإسلامية، وصياغة قراءات ورؤى متجددة متفاعلة مع روح العصر وفلسفته. جاءت هذه الدراسة في سياق الوقوف على المشهد الدعوي في بعض جوانبه التي نعتقد أنها ضرورية في تقييم وتقويم حركة الدعوة الإسلامية في مسارها الحديث، وفق منهج علمي موضوعي. تناولت-الدراسة- في مجملها موضوع التجديد في الخطاب الدعوي المعاصر من خلال استدعاء أفكار الشيخ محمد الغزالي ومنهجه في علاج قضايا الراهن الدعوي المعاصر، ووضع معالم للرؤية الإصلاحية في مختلف الميادين التي تناولها في تراثه. توزعت-الدراسة- عبر فصول أربعة: مدخل مفاهيمي تمهيدي لمفردات البحث الأساسية الخاصة بالدراسة ( الخطاب، الدعوة، التجديد..)، أما الفصل الأول فكان حول شخصية الإمام محمد الغزالي، مركزة على أهم المحطات والمنطلقات والإنتاج المعرفي والفكري في مسيرته الدعوية. وجاء الفصل الثاني معالجا لموضوع التجديد في الفكر والتصور كضرورة في خطة البحث. ناقش قضايا التجديد في علم الكلام وأساليب عرض القضايا الإيمانية والعقدية في الواقع الإنساني المعاصر، عرض بعدها على موضوع مركزية القرآن الكريم في الخطاب الدعوي، وأهمية القراءة المقاصدية لنصوص الوحي وأحكامه، ومبحث ثالث خاص بالقراءة المعاصرة لنصوص السنة النبوية المطهرة. وفي الفصل الثالث رصدت الدراسة ثلاث قضايا دعوية معاصرة ملحة في الخطاب الإسلامي: قضايا المرأة ودورها الحضاري، وموضوع التربية والتزكية ومكانته في الخطاب الدعوي المعاصر، ومبحث حول العلاقة بين الدعوة وشؤون الحكم والسياسة. خلصت الدراسة في ختامها بالتأكيد على ضرورة التجديد في الخطاب الدعوي كحتمية سننية وحضارية في مسار الدعوة الإسلامية، كما قدمت توصيات هامة حول تراث الإمام الغزالي الذي لا يزال- حسب رأيي خصبا في أسلوبه ومضمونه، ثريا للإفادة منه في قضايا الدعوة الإسلامية وشؤون النهضة والإصلاح. Abstracts Contemporary advocacy discourse is a human effort in order to clarify the faculties of Islam and its purposes at the level of the individual and the group, and it can be described as the permanent study of facts and events in the theater of human history, and their trial to the values and purposes of the final Sharia, based on the list in originality - constancy and flexibility -, constancy in principles, values, assets and flexibility In branches and means, according to strict rules of cultural knowledge, and interacting with changes and developments in various affairs and issues. The preaching discourse of Sheikh Muhammad Al-Ghazali carried a wealth of knowledge added to the balance of the Islamic call, and it contains serious and balanced attempts to direct the call, and to formulate readings and renewed visions interacting with the spirit of the era and its philosophy. He explained his description of this study, including drawing and pattern. The subject of the study dealt in its entirety with the issue of renewal in the subject of contemporary advocacy, invoking ideas on the subject of contemporary advocacy, and setting landmarks for the vision in the fight against torture in its heritage. The study was distributed through four chapters: an introductory conceptual introduction to the basic research vocabulary of the study of the study (discourse, advocacy, renewal ..), while the first chapter was about the personality of Imam Muhammad al-Ghazali, focusing on the most important stations, starting points, and knowledge and intellectual production in his advocacy career. The second chapter dealt with the topic of renewal in thought and perception 2008 in the research plan. He discussed the issues of renewal in theology and the methods of presenting faith and dogmatic issues in contemporary law, after which he presented the subject of the Holy Qur’an in the preaching discourse, and the importance of the purposeful reading of the texts of revelation and its rulings, and a third discussion on the reading of the texts of the purified Prophet’s Sunnah. In the third study, the study monitored three issues studying issues of equality in Islamic discourse: women's issues and their civilized role, the subject of education and acclamation and its place in the contemporary advocacy discourse, and a study on the relationship between the subject and politics and politics. The study concluded in the study in its conclusion definitely, and definitively in issues related to advocacy and reform.
أطروحة
Keywords: التجديد; الخطاب; الخطاب المعاصر; الدعوى; محمد الغزالي; Contemporary Discourse; Renewal; Mohammed Elghazali; suit Mohammed Elghazali